Вплив давніх *-ā-, *-jā-основ на формування іменникової словозміни західнополіських і суміжних говірок - Зінчук, Руслана Степанівна; Zinchuk, Ruslana (Східноєвропейський національний університет, 2013)
Проаналізовано формотвірну систему іменників західнополіських і суміжних говірок із огляду на вияви індуктивної дії давніх *-ā-, *-jā-основ. З’ясовано, що внутрішні взаємовпливи *-ā-, *-jā-основ та зовнішню їх дію якнайповніше відображають фіксовані в досліджуваному ареалі словоформи орудного відмінка однини субстантивів жіночого роду. Form-building noun system of Western Polissian and their neighboring dialects, which are result of inductive action of old *-ā-, *-jā-bases, is analyzed. The nouns of old *-ā-, *-jā-bases maximally saved archaic flections, substantially influencing on conjugation of other substantives. Alignment of flections is observed within a single paradigm of nouns, designed by former model *-ā-, *-jā-bases. An unification of case forms of other word modification types according to model of proper structures is noted too. It is shown that the internal mutual *-ā-, *-jā-bases and their external action more fully are reflecting of fixed in Western Polissian and their neighboring dialects of word forms of instrumental case of substantives of singular feminine. It is determined that grammatical analogy as still «alive» formative process, which often marked by close association with dialectal phonetics, significantly affects the specific dialectal word modification and identifying patterns and trends of its development.
Influence of Old *-ā-, *-jā-Bases to Form of Nounal Word Modification in Western Polissian and Their Neighboring Dialects
Keywords: західнополіські говірки; словозміна; іменник; граматична аналогія; флексія; Western Polissian dialects; word modification; noun; grammatical analogy; flection